PENGARUH SIKAP PETUGAS TERHADAP KEPATUHAN MENJAGA KEAMANAN DATA REKAM MEDIS ELEKTRONIK DI RSUD TARAKAN - Nadri Aulia Fathia; Siswati; Hosizah; Nauri Anggita Temesvari (Smart Education, 2026)
One of the factors that plays an important role in maintaining the security of EMR data is the compliance of medical record officers with applicable security procedures. However, in using EMR there are several obstacles such as a lack of skills in using technology so that officers have a dependent attitude in carrying out their duties and limited training provided. This study aims to determine the influence of officer attitudes towards compliance with maintaining the security of electronic medical record data at Tarakan Regional Hospital. The type of research used is quantitative research with a cross-sectional design. The population in this study were all 44 medical record officers. Data collection used a questionnaire with a Likert scale. The univariate data analysis technique used the three box method and bivariate data analysis using the Chi Square test. The results showed that overall the average index of all officer attitude indicators fell into the high (positive) category. In the compliance variable, the average index of all indicators fell into the high (compliant) category. The results of the Chi Square statistical test showed a significant influence between officer attitudes towards compliance with maintaining the security of EMR data at Tarakan Regional Hospital (p-Value 0.000 <0.05).